Performatywność reprezentacji - Krajewska, Anna (Przestrzenie Teorii, 2018)
Starting from a reference to René Magritte`s painting “The Images of Treachery”, the introductory article focuses on a performative understanding of representation. Pointing to the perspective of this painting, literary fiction, acting and masks, it refers to dramatic views in literary studies.